Recovery of anaerobic bacteria from clinical specimens in 12 years at two military hospitals. - Brook, I (1988)
Examination of 15,844 clinical specimens submitted over 12 years (1973 to 1985) to the anaerobic microbiology laboratories in two military hospitals demonstrated the recovery of anaerobic bacteria in 4,458 (28.1%) specimens. The specimens yielded 6,557 anaerobic isolates (1.47 isolates per specimen). Bacteroides spp. accounted for 43% of all isolates; anaerobic gram-positive cocci, 26%; Clostridium spp., 7%; and Fusobacterium spp., 4%. Bacteroides spp. predominated in abscesses, obstetrical and gynecological (OBG) infections, abdominal infections, cysts, wounds, and tumors. Members of the Bacteroides fragilis group accounted for 44% of all Bacteroides spp., and of them, B. fragilis was mostly isolated in abscesses, wounds, abdomen, and blood. Pigmented Bacteroides spp. accounted for 21% of all Bacteroides sp. isolates and were mostly isolated in sinus, eye, chest, bone, and ear infections. Bacteroides melaninogenicus accounted for 42% of this group's isolates. Bacteroides bivius accounted for 9% of Bacteroides spp., and most isolates were found in OBG infections. Anaerobic gram-positive cocci were mostly isolated in OBG infections, abscesses, and wounds. The predominant anaerobic gram-positive cocci were Peptostreptococcus magnus (18%), Peptostreptococcus asaccharolyticus (17%), Peptostreptococcus anaerobius (16%), and Peptostreptococcus prevotii (13%). Clostridium spp. were mostly isolated from wounds, abscesses, abdominal infections, and blood. The predominant strain was Clostridium perfringens (48%). Fusobacterium spp. were recovered in abscesses and abdominal and OBG infections. The predominant isolate was Fusobacterium nucleatum (47%). These data illustrate the relative frequency of the different anaerobic bacteria in a variety of infections and demonstrate the predominance of certain isolates at different sites.